Piezoelectric Actuators Mode of Vibration Influence on Energy Harvesting Applications - Perez-Alfaro, Irene; Gil Hernandez, Daniel; Sanchez Catalán, Juan Carlos; Murillo Hernandez, Nieves; Bernal Ruiz, Carlos (Jornada de Jóvenes Investigadores del I3A, 2021)
At this research, the authors have been focused on the mechanical and vibrational energy harvesting system with piezoelectric actuators. By studying the characteristics vibration modes of the piezoelectric harvester and the clamping setup configuration, a design optimization has been carried out in order to analized its influence on energy scavenging.